Rapid Tooling For Powder Injection Moulding Process - Muhammad Aslam (2016)
Injection Mould tools for various applications like polymer, wax and powder injection moulding (PIM) processes are usually manufactured with metallic materials like aluminum and tool steel which give durability and efficient functioning of moulds and good service life. Manufacturing of injection moulds is a time consuming process due to the geometric complexity of mould and strength of metallic materials. For a short prototype or pre-series run, the injection mould may be needed in a shorter time and less expenditure. For these applications, 3D printing (3DP) and Rapid Tooling (RT) technologies could be a rapid solution for fast and feasible mould development compared to a machined tool. This current study focuses on the development of powder injection moulds using 3DP with Acrylonitrile Butadiene Styrene (ABS) material. ABS 3D printed moulds can be used for design verification and a short production run for PIM process. The current study indicated that the 3D printed injection moulds development was practically fast and serve the purpose of design verification for PIM parts. Some part defects and breaking was observed due to ejection issues. Secondary RT techniques could be applied for fabricating mould that could produce parts for the production phase.